The Burden of the State: Excessive Taxation and Its Impact on Quality of Life – A Critical Perspective on PEC 45/2019 and Complementary Law 214/2025 (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
Taxation stands as one of the central pillars of state power, exerting a direct impact on the democratic structure and the guarantee of fundamental rights. This study analyzed the Brazilian tax system, focusing on the relationship between fiscal justice, human dignity, and federal balance. Employing a deductive method and constitutional analysis, the research examined how the current model of revenue collection and redistribution affects citizens' quality of life, particularly that of the most vulnerable. The results indicate that the high tax burden on consumption undermines access to essential goods and exacerbates social inequalities. The prevailing fiscal structure, characterized by the centralization of competencies and disproportionate incidence on low-income earners, weakens the effectiveness of public policies and restricts the actions of federative entities. The study identified the need for a progressive and selective taxation system, capable of respecting taxpayers' economic capacity and promoting distributive justice. It concludes that tax reform must be guided by constitutional principles, emphasizing equity, the protection of life, and the promotion of collective well-being. Taxation should cease to be an instrument of exclusion and instead function as a vector for sustainable development, ensuring that all citizens live with dignity throughout all phases of existence.